Lithuanian Language and Literature Program – a Medium for Deep Reading Education - Arūnas Šileris (Knygotyra, 2022)
Researchers have been observing the deteriorating deep reading skills among pupils and highlighting the necessity to nurture them. Yet the concept of what ‘reading’ means (and ‘deep reading’ in particular) seems elusive. Deep reading may be interpreted in a number of ways. The difference in the notion of what constitutes deep reading calls for a closer investigation, with the view to delineating the two concepts.